L2 Writing Assistants and Context-Aware Dictionaries: New Challenges to Lexicography - Tarp, Sven; Fisker, Kasper; Sepstrup, Peter (Lexikos, 2017)
Dictionaries are increasingly integrated into other tools designed to assist the reading, writing and translation of texts. Write Assistant is a newly developed tool aimed at assisting people writing in a second language. It feeds on big data taken in from corpora and digital dictionaries. The paper discusses the philosophy behind the tool, the techniques applied, its empirical basis and functionality, as well as the extent to which it helps its users. It shows how the tool makes it possible to shorten and even skip some phases in the traditional information-search process and allows its user to maintain the focus on the message to be written without the need to consult external information resources. The paper shows how the underpinning technology gives birth to a new type of dictionary that is context-aware and provides a more personalised user service. But it also indicates that future dictionaries need to be conceptionally adapted to the specific tool in order to optimize the service. All this poses new challenges to lexicography.